History of Islam Umar ibn al-khattab (R.A) - Aziz, Maulvi Abdul (Riyadh : Darussalam, 2012)
"History of Islam: Umar ibn al-Khattab (R.A)" by Maulvi Abdul Aziz is the second installment in Darussalam's "History of Islam" series, focusing on the life and leadership of Umar ibn al-Khattab, the second Caliph of Islam. This volume is designed to provide readers, especially Muslim youth, with an authentic and engaging account of Umar's pivotal role in early Islamic history.
Keywords: History : Islam